Hermeneutika Pesan Dakwah dalam Kumpulan Cerpen “Dari Ave Maria ke Jalan Lain ke Roma” - Mustafirin; Agus Riyadi (Jurnal Komunikasi Islam, 2021)
This study aims to examine the moral teachings contained in the collection of short stories (cerpen) of Idrus. By using hermeneutic analysis, this study shows that Idrus’ short stories convey moral teachings regarding patriotism, nationalism, lifestyle, social criticism, and faith in Allah Swt. Specifically, these teachings encompases sincerity, fortitude fortitude where calamity is a warning and a trial from Allah swt., teachings about justice and believing in Allah as well as Muhammad is the messenger of Allah swt. Although the da’wah material conveyed through these writings was produced in accordance with the demands of the social conditions of the people at that time, namely the Japanese occupation period, it is still relevant today.